Determinants for Sustainable Entrepreneurial Intentions: A Systematic Literature Review - Usman, Malik; Usman, Muhammad; Wasim, Muhammad; Habib, Aymen (iRASD Journal of Economics, 2024)
Sustainable entrepreneurship has emerged as a vibrant domain within the field of entrepreneurship, especially in recognition of ecological issues, entrepreneurship is a solution to environmental problems now a day. Substantial studies have been conducted to understand the phenomena of sustainable entrepreneurship. This review aims to provide theoretical basis for understanding scholarly thoughts, which highlights some key determinants of sustainable entrepreneurial intentions. Based on Theory of Planned Behavior (TPB) (Ajzen, 1991) and Shapero’s (1982), Entrepreneurial event model (EEM), this review analyzes literature and discusses the main antecedent, which elaborates our collective understanding about the nature of sustainable entrepreneurial intentions. The review critically discusses the dominant approaches which foster the research on sustainable entrepreneurship in theory and practice.